Color, pH, and Yolk Index of Chicken Eggs Coated with Coriander at Different Curing Time - Dian Septinova; Dinda Permata Putri; Riyanti Riyanti; Khaira Nova (JURNAL ILMIAH PETERNAKAN TERPADU, 2023)
This study aims to determine the effect of the length of salting of purebred chicken eggs covered with ingredients containing coriander (Coriandrum sativum L.) on color, pH, and yolk index. The study used a completely randomized design (CRD) with salting time (1, 7, 14, and 21 days) as the treatment, each consisting of 5 replications. Data were analyzed for variance and Least Significant Differnce (LSD) at the 5% level. The results showed that salting time had a significant effect (P>0,05) on color and index yolk, but no significant effect (P>0,05) on the pH of the yolk. Salting eggs for 14 days produced the best yolk color, while 21 days of salting produced the best yolk index and pH. The conclusion is that the salting time for making salted egg covered with coriander-containing ingredients is at least 21 days.